MANAJEMEN STRATEGI DALAM MENINGKATKAN JUMLAH PESERTA DIDIK DI MADRASAH TSANAWIYAH SWASTA AR RIDHA MEDAN MARELAN - Misnan; Muhammad Irfan; Dedi Antono Sihombing (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2023)
Abstract: This study aims at a strategy to increase the number of students among the ever-growing numer of new students in one of Marelan islamic school. Research design is research design is and, and in this research as confined to thr product stage leading to strategic planning to increase the number of students, Research for collection are observations, REAs and research papers. Data analysis was utilized to establish methods for increasing the number of enrollable students by using (SWOT) analysis to examine internal and external elements, such as school strengths, weaknesses, opportunities, and threats. Our institution is in the SO quadrant as a result of the SWOT analysis (Strength Opportunity), and we take advantage of the strengths of the school's internal environment to seize opportunities from the external environment and support aggressive strategies. A proposed competitive strategy for school planning is: (1) Teachers meet the criteria i.e. bachelor's degree and teach in their respective subject areas. She is the only teacher without a degree. (2) High teacher morale and dedication to educational service; (3) The infrastructure is fairly complete with proper laboratories. (4) Good coordination with the local environment. Keyword : Strategy, Strengths, Weaknesses